2020
DOI: 10.1007/s00428-020-02940-3
|View full text |Cite
|
Sign up to set email alerts
|

Expanding spectrum of “spitzoid” lesions: a small series of 4 cases with MAP2K1 mutations

Abstract: The molecular background of a significant proportion of spitzoid neoplasms is still unknown. Recently, activating mutations in MAP2K1 have been described in a few spitzoid lesions, but not in benign Spitz nevi. We report four cases of melanocytic tumors with spitzoid features in which a MAP2K1 mutation was detected. The lesions did not show a single distinct phenotype and ranged from benign to malignant. Two cases resembled desmoplastic Spitz nevi. Based on the combination of morphological, immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 14 publications
(20 reference statements)
1
35
1
Order By: Relevance
“…As oncogenic gene alterations other than kinase gene fusions, HRAS point mutations are found in approximately 15% of all Spitz neoplasms 8 . In addition, more recent studies reported MAP2K1 mutations in a subset of spitzoid lesions 4,9‐11 . All these genetic anomalies are present in a mutually exclusive pattern.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…As oncogenic gene alterations other than kinase gene fusions, HRAS point mutations are found in approximately 15% of all Spitz neoplasms 8 . In addition, more recent studies reported MAP2K1 mutations in a subset of spitzoid lesions 4,9‐11 . All these genetic anomalies are present in a mutually exclusive pattern.…”
Section: Introductionmentioning
confidence: 96%
“…8 In addition, more recent studies reported MAP2K1 mutations in a subset of spitzoid lesions. 4,[9][10][11] All these genetic anomalies are present in a mutually exclusive pattern. Herein, we present the first case of Spitz nevus with a NTRK2 rearrangement, which is a novel TFG-NTRK2 fusion.…”
mentioning
confidence: 99%
“…In more recent years, genomic studies have shown that most Spitz neoplasms harbor serine–threonine kinase mutations (HRAS, or more rarely MAP2K1) or receptor tyrosine and serine–threonine kinase fusions (ALK, ROS1, NTRK1, NTRK3, MAP3K8, more rarely BRAF, RET, MET, NTRK2, ERB4, FGFR1, MAP3K3, PRKDC) [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Of note, BRAF or MAP3K8-fused cases may pursue a more aggressive course compared with tyrosine kinase–fused cases, especially in the presence of TERT promoter mutations.…”
mentioning
confidence: 99%
“…The diagnosis of Spitz tumors may be difficult on clinical, dermoscopic, and histologic grounds [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Clinically, they may present either as pigmented, hypopigmented, or non-pigmented lesions.…”
mentioning
confidence: 99%
See 1 more Smart Citation